Research on quantitative risk assessment of fuel leak of LNG-fuelled ship during lock transition process. (May 2022) - Xie, Cheng; Huang, Liwen; Wang, Rui; Deng, Jian; Shu, Yaqing; Jiang, Dan
Highlights: An QRA model to assess fuel leak of LNG-fuelled ship during lockage is proposed. HAZOP-LOPA methodology is used to obtain LNG leak probabilities. The frequencies of initiating event are calculated based on Bayesian estimation. LNG leak consequences are simulated using CFD model. QRA results show the individual risk are within the acceptable range. Abstract: As a clean and efficient new maritime fuel, the strict emission standards worldwide recently have been stimulating the use of Liquefied nature gas (LNG), leading a great increase in the number of LNG-fuelled ship. Due to the hazard characteristics of freezing and flammability after release inside a ship lock, it may cause fire and explosion consequence which may threaten the safety of people and lock structure, the research on quantitative risk assessment (QRA) of fuel leakage during lockage is urgently needed in the safety management of LNG-powered ship and ship lock. This paper proposes an integrated QRA model for analysing the fuel leakage risk during lockage of LNG-fuelled ship, and the QRA process based on the world's largest lock Three Gorges lock is performed including the risk identification, probability calculation and consequence modelling. The results show that the individual risks (IRs) of LNG-fuelled ship during lockage is within the negligible area, and the main threat of LNG leakage is heat radiation rather than overpressure. The research results of the study can provide theoretical support in policy-making process of LNG-fuelled ship and ship lock.